Career paths of Swedish top-level women soccer players. (18th August 2019) - Andersson, Rebecca; Barker-Ruchti, Natalie
Abstract: This study explores seven Swedish top-level women's soccer players' career development experiences. Data were produced through semi-structured interviews and a biographical mapping grid. The theoretical framework of 'careership' was employed to understand the data. The results showed homogenous career paths. Moreover, the data show that the players decided at a young age to pursue a career in soccer; experienced the transition from junior to senior level soccer as difficult because of a lack of physical preparedness; soccer over school commitments. We recommend that soccer stakeholders (e.g. federations, clubs, coaches) give the transition from junior to senior level soccer special attention to prevent intense demands that may cause dropout. We further propose that if athletes should give sport and education equal priority, the Swedish dual career concept of high school education and sport needs further reflection and adjustment.